ANALISIS WACANA KRITIS REPRESENTASI PERILAKU MYTHOMANIA DAN KOMUNIKASI INTERPERSONAL PADA TOKOH GEMA DALAM FILM "TINGGAL MENINGGAL" - Maria Natalia Owa; Tira Fitriawardhani; Julyanto Ekantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of lying in interpersonal communication is increasingly common in social life and has the potential to develop into mythomania, or pathological lying. This behavior occurs not only in real life but is also portrayed in film as a reflection of the social reality of modern society. The film Tinggal Meninggal presents the character Gema as an individual who repeatedly uses lies to gain attention and social acceptance. This study aims to analyze the representation of mythomania and interpersonal communication in the character of Gema. The research employed a descriptive qualitative method with Norman Fairclough's Critical Discourse Analysis approach, covering three dimensions: text, discursive practice, and social practice. Primary data in the form of dialogue, scenes, and verbal-nonverbal interaction were collected through repeated observation and documentation, then analyzed across eight key scenes representing the escalation of lies from simple to complex forms. The results show that Gema's mythomanic behavior is represented through manipulative interpersonal communication, supported by narrative fabrication, nonverbal cues, and social media to construct a self-image within the social environment. At the level of discursive practice, the lies are produced consistently and accepted by the social environment through collective empathic responses. At the level of social practice, the film represents a condition of modern society that tends to grant attention based on tragedy and social validation, making lying a tool for gaining recognition from the surrounding community.